Heat treatment method for equiaxing laser cladding formed near-alpha type titanium alloy

Through multi-stage heat treatment, the structural structure of titanium alloy is regulated, and the problem of difficulty in eliminating residual stress and anisotropy in the isoxidation process of titanium alloy in additive manufacturing is solved, and the high strength and excellent mechanical properties of titanium alloy are achieved.

CN120193273AActive Publication Date: 2025-06-24NORTHWEST NONFERROUS METALS BAOJI INNOVATION INSTITUTE +3
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510608384.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-13
Publication Date
2025-06-24
Estimated Expiration
2045-05-13

AI Technical Summary

Technical Problem

The existing isoxidation process of additively manufactured titanium alloys is difficult to effectively eliminate residual stress and anisotropy generated during laser overlay forming, resulting in insufficient comprehensive mechanical properties of the material.

Method used

Multi-stage heat treatment methods, including annealing, slow cooling, solid solution and aging, regulate the morphology and content of the titanium alloy and the α phase, and obtain an isometric or bistate structure composed of isometric α and residual β.

Benefits of technology

Effectively eliminate residual stress and anisotropy, improve the tensile strength and elongation after break of titanium alloy, and improve its comprehensive mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120193273A_ABST
    Figure CN120193273A_ABST
Patent Text Reader

Abstract

The invention discloses a heat treatment method for equiaxing a near-alpha type titanium alloy formed by laser cladding, the near-alpha type titanium alloy comprises the following components in percentage by mass: 5.0%-8.0% of Al, 2.0%-5.0% of Mo, 1.0%-3.0% of Zr, 0.1%-1.0% of Si, 0.1%-1.0% of x, x is less than or equal to 0.5%, x is other impurity elements including Fe, C, N, H and O, and the balance is Ti, and the heat treatment method comprises annealing, slow cooling, solid solution and aging. According to the method, the structure of the near-alpha type titanium alloy formed through laser cladding and the morphology and content of the alpha phase are regulated and controlled through multi-stage heat treatment, an equiaxial structure or a double-state structure composed of equiaxial alpha and residual beta is obtained, and residual stress and anisotropy generated in the laser cladding forming process of the near-alpha type titanium alloy are effectively eliminated; the composite material is suitable for the fields of aerospace, ocean engineering, petrochemical engineering, transportation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of titanium alloy heat treatment, and particularly relates to a heat treatment method for equiaxed transformation of laser cladding formed near-α titanium alloy. Background Art

[0002] Titanium alloys are widely used in important fields such as aerospace, ocean engineering, petrochemical industry, etc. During the additive manufacturing process of titanium alloys, due to the characteristics of layer-by-layer stacking and rapid solidification, columnar β grains growing along the deposition direction are easily formed, resulting in significant anisotropy of the microstructure. At the same time, non-equilibrium phases such as needle-like α' martensite and Widmanstätten structure are easily formed during the rapid solidification process. The presence of these brittle phases reduces the plasticity and toughness of the material.

[0003] Equiaxed grains have similar sizes in three-dimensional directions, significantly reducing the anisotropy commonly found in additive manufacturing, and making the strength, plasticity, and toughness of the material tend to be consistent in different directions. The uniform distribution of equiaxed grains can hinder the crack from propagating along a single direction, making the crack propagation path more tortuous, consuming more energy, thereby prolonging the fatigue life, improving the fracture resistance of the material, and enhancing the structural safety. Therefore, titanium alloys with equiaxed grains are suitable for fields with strict multi-directional mechanical property requirements such as aerospace and medical implants, reducing the failure risk caused by directional differences. In summary, the application of equiaxed microstructure in additive manufacturing titanium alloys can improve the comprehensive performance of the material. Therefore, the optimization of process parameters for equiaxed transformation of additive manufacturing titanium alloys will further promote its industrial application. Summary of the Invention

[0004] The technical problem to be solved by the present invention is to provide a heat treatment method for equiaxed transformation of laser cladding formed near-α titanium alloy in view of the deficiencies of the above-mentioned prior art. This method controls the microstructure, morphology, and content of α-phase of the laser cladding formed near-α titanium alloy through multi-stage heat treatment including annealing, slow cooling, solution treatment, and aging, obtaining an equiaxed microstructure or duplex microstructure composed of equiaxed α and residual β, effectively eliminating the residual stress and anisotropy generated during the laser cladding forming process of the near-α titanium alloy, improving its comprehensive mechanical properties, and solving the need for equiaxed transformation of existing additive manufacturing titanium alloys.

[0005] To solve the above technical problems, the technical solution adopted by the present invention is as follows: A heat treatment method for equiaxedization of a laser cladding formed near-α type titanium alloy, characterized in that the near-α type titanium alloy comprises the following components in mass percentage: Al 5.0% - 8.0%, Mo 2.0% - 5.0%, Zr 1.0% - 3.0%, Si 0.1% - 1.0%, x ≤ 0.5%, where x is other impurity elements including Fe, C, N, H, O, and the balance is Ti. This heat treatment method obtains a high-strength laser cladding formed near-α type titanium alloy by performing multi-stage heat treatment on the laser cladding formed near-α type titanium alloy, including annealing, slow cooling, solution treatment, and aging, to regulate the microstructure and the morphology and content of the α phase of the laser cladding formed near-α type titanium alloy.

[0006] Generally, the raw materials used for preparing the laser cladding formed near-α type titanium alloy of the present invention are titanium alloy powders, and there is no binding or caking phenomenon in the titanium alloy powders, and they have good sphericity, no pores on the powder surface, and the particle size is mainly 80μm - 110μm.

[0007] The laser cladding forming process parameters of the laser cladding formed near-α type titanium alloy of the present invention are: laser power 6kW - 8kW, scanning speed 800mm / min - 1200mm / min, powder feeding speed 1000g / H - 1200g / H, and overlapping ratio 30% - 50%.

[0008] The above-mentioned heat treatment method for equiaxedization of a laser cladding formed near-α type titanium alloy is characterized in that the heat treatment comprises the following steps:

[0009] Step 1: Heat the laser cladding formed near-α type titanium alloy to 500°C - 600°C and hold for 4h - 10h for annealing, and then air cool.

[0010] Step 2: Heat the laser cladding formed near-α type titanium alloy air-cooled in Step 1 to T β -10°C and hold for 1h - 4h, and then slow cool; the T β is the β phase transformation point temperature of the laser cladding formed near-α type titanium alloy, in °C;

[0011] Step 3: Solution-treat the laser cladding formed near-α type titanium alloy slow-cooled in Step 2 at T β -20°C to T β -150°C for 1h - 4h, and then air cool;

[0012] Step 4: Heat the laser cladding formed near-α type titanium alloy air-cooled in Step 3 at 400°C - 700°C for 4h - 8h, and then air cool to obtain the heat-treated laser cladding formed near-α type titanium alloy.

[0013] The above heat treatment method for equiaxed transformation of laser cladding formed near-α titanium alloy is characterized in that, in step two, the cooling rate of slow cooling is not faster than 30°C / min, and the cooling termination temperature is lower than the α+β phase region temperature, which is beneficial to the equiaxialization of the α phase.

[0014] The above heat treatment method for equiaxed transformation of laser cladding formed near-α titanium alloy is characterized in that the heating and slow cooling processes described in step two are repeated multiple times until the α phase reaches the target equiaxed degree through phase transformation.

[0015] The above heat treatment method for equiaxed transformation of laser cladding formed near-α titanium alloy is characterized in that the laser cladding formed near-α titanium alloy after heat treatment in step four has an equiaxed structure or duplex structure composed of equiaxed α and residual β.

[0016] The above heat treatment method for equiaxed transformation of laser cladding formed near-α titanium alloy is characterized in that the room temperature mechanical properties of the laser cladding formed near-α titanium alloy after heat treatment are: tensile strength Rm≥1000MPa, and elongation after fracture A≥8%.

[0017] The present invention has the following advantages compared with the prior art:

[0018] 1. By performing multi-stage heat treatment on the laser cladding formed near-α titanium alloy, the present invention regulates the microstructure, morphology and content of the α phase of the laser cladding formed near-α titanium alloy, obtains an equiaxed structure or duplex structure composed of equiaxed α and residual β, effectively eliminates the residual stress and anisotropy generated during the laser cladding forming process of the near-α titanium alloy, and obtains a laser cladding formed near-α titanium alloy with excellent comprehensive mechanical properties.

[0019] 2. The present invention performs multi-stage heat treatment on the laser cladding formed near-α titanium alloy, including annealing, slow cooling, solution treatment and aging. Through stress relief annealing and multi-stage heating and slow cooling treatment, and controlling the slow cooling rate to achieve a low degree of supercooling, and the low degree of supercooling is the dominant condition for the precipitation of the α phase, thereby regulating the aspect ratio of the α phase and suppressing the precipitation of α, s achieving the purpose of spheroidizing the α phase, realizing equiaxialization and avoiding the anisotropy of lamellar α. Then, through solution + aging treatment, the content and size of the α phase in the titanium alloy are regulated, and the synergistic effect of precipitation strengthening and fine grain strengthening is utilized to finally realize the optimized regulation of the comprehensive mechanical properties of the laser cladding formed near-α titanium alloy. s

[0020] 3. The room temperature mechanical properties of the laser cladding formed near-α titanium alloy after heat treatment in the present invention are: tensile strength Rm≥1000MPa, and elongation after fracture A≥8%. It has high strength characteristics and has wide application value in the fields of aerospace, ocean engineering, petrochemical industry, transportation, etc.

[0021] ​The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Description of the Drawings

[0022] Figure 1 It is the metallographic structure diagram of the laser cladding formed near-α type titanium alloy after heat treatment in Embodiment 1 of the present invention.

[0023] Figure 2 It is the metallographic structure diagram of the laser cladding formed near-α type titanium alloy after heat treatment in Embodiment 2 of the present invention. Detailed Embodiments

[0024] Embodiment 1

[0025] The nominal composition of the laser cladding formed near-α type titanium alloy in this embodiment is Ti-6Al-3Mo-1.5Zr-0.3Si, including the following components by mass percentage: Al 6%, Mo 3%, Zr 1.5%, Si 0.3%, x≤0.5%, where x is other impurity elements including Fe, C, N, H, O, and the balance is Ti.

[0026] The laser cladding forming process parameters of this laser cladding formed near-α type titanium alloy are: laser power 6kW, scanning speed 1000mm / min, powder feeding speed 1000g / H, and overlap ratio 30%.

[0027] The equiaxed heat treatment method of the laser cladding formed near-α type titanium alloy in this embodiment includes the following steps:

[0028] Step 1: Heat the laser cladding formed near-α type titanium alloy to 540°C and hold for 6h for annealing, and then air cool;

[0029] Step 2: Heat the laser cladding formed near-α type titanium alloy air-cooled in Step 1 to 1005°C and hold for 1h, and then cool it to 500°C at a cooling rate of 5°C / min. Repeat the heating and holding and slow cooling processes twice, for a total of three times;

[0030] Step 3: Solutionize the laser cladding formed near-α type titanium alloy after the third slow cooling in Step 2 at 890°C for 2h, and then air cool to room temperature;

[0031] Step 4: Hold the laser cladding formed near-α type titanium alloy air-cooled in Step 3 at 530°C for 6h, and then air cool to obtain the laser cladding formed near-α type titanium alloy after heat treatment.

[0032] Figure 1 It is the metallographic structure diagram of the laser cladding formed near-α type titanium alloy after heat treatment in this embodiment. From Figure 1 It can be seen that the laser cladding formed near-α type titanium alloy after heat treatment has an equiaxed structure composed of equiaxed α and residual β.

[0033] After testing, the room-temperature mechanical properties of the laser cladding formed near-α titanium alloy after heat treatment in this example are: tensile strength Rm = 1085 MPa, and elongation after fracture A = 14.5%.

[0034] Example 2

[0035] The nominal composition of the laser cladding formed near-α titanium alloy in this example is Ti-7.8Al-4Mo-2Zr-0.3Si, including the following components by mass percentage: Al 7.8%, Mo 4%, Zr 2%, Si 0.3%, Fe 0.2%, x ≤ 0.3%, where x is other impurity elements including Fe, C, N, H, O, and the balance is Ti;

[0036] The laser cladding forming process parameters of this laser cladding formed near-α titanium alloy are: laser power 6 kW, scanning speed 1000 mm / min, powder feeding speed 1000 g / H, and overlap ratio 30%.

[0037] The equiaxed heat treatment method of the laser cladding formed near-α titanium alloy in this example includes the following steps:

[0038] Step 1: Heat the laser cladding formed near-α titanium alloy to 540 °C and hold for 6 h for annealing, and then air cool;

[0039] Step 2: Heat the laser cladding formed near-α titanium alloy air-cooled in Step 1 to 1005 °C and hold for 1 h, and then slowly cool to room temperature at a cooling rate of 0.5 °C / min;

[0040] Step 3: Solutionize the laser cladding formed near-α titanium alloy slowly cooled in Step 2 at 990 °C for 2 h, and then air cool to room temperature;

[0041] Step 4: Hold the laser cladding formed near-α titanium alloy air-cooled in Step 3 at 650 °C for 6 h, and then air cool to obtain the laser cladding formed near-α titanium alloy after heat treatment.

[0042] Figure 2 This is the metallographic structure diagram of the laser cladding formed near-α titanium alloy after heat treatment in this example. From Figure 2 It can be seen that the laser cladding formed near-α titanium alloy after heat treatment has a duplex structure composed of equiaxed α and residual β.

[0043] After testing, the room-temperature mechanical properties of the laser cladding formed near-α titanium alloy after heat treatment in this example are: tensile strength Rm = 1113 MPa, and elongation after fracture A = 11.5%.

[0044] The above are only the preferred embodiments of the present invention and do not impose any limitations on the present invention. Any simple modifications, changes, and equivalent variations made to the above embodiments based on the technical essence of the invention still fall within the protection scope of the technical solution of the present invention.

Claims

1. A heat treatment method for isoaxialization of near-α-type titanium alloy formed by laser cladding, characterized in that: The near-α-type titanium alloy includes the following components in percentage by mass: Al 5.0% to 8.0%, Mo 2.0% to 5.0%, Zr 1.0% to 3.0%, Si 0.1% to 1.0%, x≤0.5%, x is other impurity elements including Fe, C, N, H, O, and the balance is Ti. The heat treatment method performs multi-stage heat treatment including annealing, slow cooling, solid solution and aging on the laser cladding formed near-α-type titanium alloy to adjust the organization of the laser cladding formed near-α-type titanium alloy and the morphology and content of the α phase, so as to obtain a high-strength laser cladding formed near-α-type titanium alloy.

2. The heat treatment method for isoaxialization of near-α-type titanium alloy formed by laser cladding according to claim 1 is characterized in that: The heat treatment comprises the following steps: Step 1: heating the laser cladding formed near-α titanium alloy to 500°C to 600°C and keeping the temperature for 4h to 10h for annealing, followed by air cooling; Step 2: Heat the laser cladding formed near-α titanium alloy after air cooling in step 1 to T β -10℃ for 1h~4h, then slowly cooled; β is the β phase transition temperature of the near-α titanium alloy formed by laser cladding, in °C; Step 3: The laser cladding formed near-α titanium alloy after slow cooling in step 2 is placed on T β -20℃~T β -150℃ for 1h~4h to carry out solid solution, followed by air cooling; Step 4: The laser cladding formed near-α titanium alloy after air cooling in step 3 is kept at 400° C. to 700° C. for 4 h to 8 h, and then air cooled to obtain the laser cladding formed near-α titanium alloy after heat treatment.

3. The heat treatment method for isoaxialization of near-α-type titanium alloy formed by laser cladding according to claim 2 is characterized in that: The slow cooling rate in step 2 is no faster than 30°C / min, and the cooling termination temperature is lower than the temperature of the α+β phase region, which is conducive to the equiaxed α phase.

4. The heat treatment method for isoaxialization of near-α-type titanium alloy formed by laser cladding according to claim 2 is characterized in that: The heating and slow cooling process in step 2 is repeated multiple times until the α phase reaches the target equiaxed degree through phase transformation.

5. The heat treatment method for isoaxialization of near-α-type titanium alloy formed by laser cladding according to claim 2 is characterized in that: The laser cladding formed near-α titanium alloy after the heat treatment in step 4 has an equiaxed structure or a dual structure consisting of equiaxed α and residual β.

6. The heat treatment method for isoaxialization of a near-α-type titanium alloy formed by laser cladding according to claim 2, characterized in that: The room temperature mechanical properties of the laser cladding formed near-α-type titanium alloy after the heat treatment are as follows: tensile strength Rm≥1000MPa, elongation after fracture A≥8%.

Citation Information

Patent Citations

  • Efficient laser additive manufacturing titanium alloy and heat treatment method for improving anisotropy of titanium alloy

    CN115609007A

  • Titanium alloy for golf-club face

    JP2012132057A

  • Titanium alloy parts produced using solid state additive manufacturing

    WO2025064807A1